2014
DOI: 10.1089/acm.2014.5368.abstract
|View full text |Cite
|
Sign up to set email alerts
|

Active, Self-Care Complementary and Integrative Medicine Therapies for the Management of Chronic Pain Symptoms: A Rapid Evidence Assessment of the Literature

Abstract: Purpose: With the recent developments in evidence-based complementary medicine, the Indian systems of medicine (ISM) with its multimodal individualized treatment, perceives many challenges in conducting randomized controlled trials (RCTs). A clear understanding of these challenges is a basic step in determining the feasibility of RCTs and development of research methods in this field. The aim of our study was to identify the important methodological considerations specific for ISM (Ayurveda and Siddha) in cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The effects of CBMs (e.g., nabilone, dronabinol, and THC analogue) and smoked cannabinoids were examined in several recent RCT studies; the appraising of those studies in 3 different reviews revealed overall evidence that cannabinoids are safe and moderately effective for the investigated diagnoses (21)(22)(23). Furthermore, the 3 most recent reviews of RCTs T T he treatment of chronic pain is based on a combination of pharmacotherapy and complementary non-pharmacotherapy treatment (1)(2)(3). The approach for pharmacological treatment for the relief of chronic pain is based primarily on pain intensity.…”
Section: Cannabinoids: Clinical Trials Reviews and Meta-analyses Chmentioning
confidence: 99%
“…The effects of CBMs (e.g., nabilone, dronabinol, and THC analogue) and smoked cannabinoids were examined in several recent RCT studies; the appraising of those studies in 3 different reviews revealed overall evidence that cannabinoids are safe and moderately effective for the investigated diagnoses (21)(22)(23). Furthermore, the 3 most recent reviews of RCTs T T he treatment of chronic pain is based on a combination of pharmacotherapy and complementary non-pharmacotherapy treatment (1)(2)(3). The approach for pharmacological treatment for the relief of chronic pain is based primarily on pain intensity.…”
Section: Cannabinoids: Clinical Trials Reviews and Meta-analyses Chmentioning
confidence: 99%
“…CNCP treatment is based on combinations of pharmaceutical analgesics (non-steroidal anti-inflammatory drugs (NSAIDs), anticonvulsants, antidepressants, but mostly by opioids ( Chou et al, 2009 ) and complementary non-pharmacotherapy treatment (e.g. physical therapy, dry needling, behavioral therapy) ( Cherkin et al, 2014 ; Lee et al, 2014 ). Nevertheless, as the 'opioid crisis' continues ( Volkow and Collins, 2017 ), newer, safer options for the treatment of CNCP merit investigation.…”
Section: Introductionmentioning
confidence: 99%